2007
DOI: 10.1055/s-2008-1060335
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Musculoskeletal Nuclear Medicine

Abstract: This article reviews the current role of nuclear medicine in common benign and malignant pediatric musculoskeletal conditions and discusses future applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, malignant disease such as leukemia and sarcoma may mimic acute osteomyelitis. 1,5 Blood flow, blood pool, and delayed images show focally high uptake in the affected bone ( Fig. 4).…”
Section: Benign Etiologymentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, malignant disease such as leukemia and sarcoma may mimic acute osteomyelitis. 1,5 Blood flow, blood pool, and delayed images show focally high uptake in the affected bone ( Fig. 4).…”
Section: Benign Etiologymentioning
confidence: 96%
“…It offers better sensitivity by improving the spatial resolution because the PET scanner has a greater ability than the gamma camera to image highenergy photons of 18 F-NaF. 5,6 Recently, a prospective pilot study showed the feasibility of performing a single PET/CT scan using a combined administration of 18 F/ 18 F-FDG for adult cancer detection. 14…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a sensitive method to detect alteration of bone metabolism of any cause and should be correlated with the patient's clinical history and other test results because of its low specificity (12)(13)(14). Hybrid imaging with CT, such as SPECT/CT and PET/CT, improves specificity and diagnostic accuracy.…”
Section: Value Of Pediatric Nuclear Medicinementioning
confidence: 99%